The Effects of the Coffee Trademarking Initiative and Starbucks Publicity on Export Prices of Ethiopian Coffee - Aslıhan Arslan; Christopher Phillip Reicher (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2010)
The Ethiopian government initiated the Ethiopian Coffee Trademarking and Licensing Initiative in 2004 for three coffee origins: Sidama, Yirgacheffe and Harar. Following a court case between Starbucks and the Ethiopian government regarding this initiative, Oxfam organized a publicity campaign. This paper evaluates the effect of these interventions on the export prices of trademarked Ethiopian coffees. We find that the prices of the trademarked coffees increased by about 10% following these interventions. The magnitude of this change is comparable with the farm gate prices reported in the literature; however, we cannot establish direct causation or observe the passthrough into farm gate prices.
Keywords: O13; F14; 330; Trademarks; coffee prices; Ethiopia